2017
DOI: 10.1267/ahc.17004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-kit and Cytokeratin 5 in the Submandibular Gland after Release of Long-Term Ligation of the Main Excretory Duct in Mice

Abstract: Long-term submandibular duct obstruction is thought to cause irreversible atrophy and dysfunction of the submandibular gland. As an atrophic gland may be induced clinically by chronic or recurrent infection, it is generally removed surgically. However, the regenerative capacity of atrophic submandibular glands after long-term obstruction is not completely understood. We studied the regenerative capacity of the mouse submandibular duct using an aneurysm clip ligation model. We documented changes in the size, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The expression of c-kit, a salivary gland stem cell marker 12,36) , did not exhibit a significant difference between the groups, whereas the expression of precursor cell marker CK5 14,37) was significantly high in the CM group at 4 weeks after the release. Furthermore, the expression of an acinar cell marker, AQP5 8,38,39) , was significantly high in the CM group at 8 weeks after the release.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The expression of c-kit, a salivary gland stem cell marker 12,36) , did not exhibit a significant difference between the groups, whereas the expression of precursor cell marker CK5 14,37) was significantly high in the CM group at 4 weeks after the release. Furthermore, the expression of an acinar cell marker, AQP5 8,38,39) , was significantly high in the CM group at 8 weeks after the release.…”
Section: Discussionmentioning
confidence: 79%
“…There have been numerous studies on the salivary gland tissue after ligation and ligation release as a model of duct obstruction by salivary gland stones [5][6][7][8] . The atrophied salivary glands after ligation release express stem cell and progenitor cell markers and exhibit the remaining self-renewal capacity [9][10][11][12][13][14] . Therefore, adaptation of the salivary gland tissue to regenerative medicine has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that Ror1 plays essential roles in tissue-and organogenesis during embryonic development and cancer progression (Endo et al, 2015;Minami et al, 2010), its roles in tissue-damage responses have not been reported, except for our recent finding about the critical role of Ror1 during regeneration of the injured skeletal muscles (Kamizaki et al, 2017). Since the SMGs have capacity to regenerate after long-term obstruction (Watanabe et al, 2017), it would be of interest to examine a possible functional implication of Ror1 in regeneration of the damaged SMGs.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies revealed a marked decrease (75%) in the weight of the salivary gland after experimental obstruction [ 17 , 83 , 84 , 85 ]. The dramatic atrophy could make it more difficult to identify the obstructed gland and then to stitch out the tightly knotted silk without causing any ductal damage [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the past, rats were more frequently used as experimental animals for clipping than mice, probably because of the surgical feasibility, whereas experimental mice were considered to have unique advantages of well-identified genetic backgrounds over other animals. However, since the introduction of the mini-clip, the mouse has been more actively used by overcoming the limitation of size [ 78 , 84 ]. The location of the experimental obstruction is grossly divided into the proximal ductal portion through the extraoral or cervical approach and the distal ductal portion through the intraoral approach [ 81 , 85 ].…”
Section: Resultsmentioning
confidence: 99%